Advances in molecular genetics for pulmonary atresia. (22nd September 2016) - Gao, Manchen; He, Xiaomin; Zheng, Jinghao
Abstract: Genetic and environmental factors may be similar in certain CHD. It has been widely accepted that it is the cumulative effect of these risk factors that results in disease. Pulmonary atresia is a rare type of complex cyanotic CHD with a poor prognosis. Understanding the molecular mechanism of pulmonary atresia is essential for future diagnosis, prevention, and therapeutic approaches. In this article, we reviewed several related copy number variants and related genetic mutations, which were identified in patients with pulmonary atresia, including pulmonary atresia with ventricular septal defect and pulmonary atresia with intact ventricular septum.